A methodology of photovoltaic power integration in air conditioning system – An inverter‐less approach. Issue 3 (30th March 2022) - Das, Dhiman; Mishra, Sukumar; Singh, Bhim
Abstract: The photovoltaic (PV) power generation and cooling demand of the air conditioner are increased along with an increase in solar irradiation. Therefore, considering such fact, in this paper, PV power is integrated with the air conditioner to support the grid. With recent developments in power electronics, the air conditioning systems are operated in variable speed using variable frequency drive (VFD) technology. In this paper, taking the advantage of the VFD technology, PV power is directly injected into the DC bus of VFD using an isolated DC‐DC converter. In this methodology, due to the high‐frequency DC‐DC conversion, high power DC‐AC (50 Hz) stage is eliminated, and seamless power is transferred from PV generation to the load without interrupting the main operation of the air conditioner. Thus, the reliability of the system is enhanced with the reduction in overall cost, conversion losses and bulkiness. With the PV power support, the peak amplitude of the grid current is reduced and consequently the power consumption, reactive power intake from the grid, as well as the harmonics component of the grid current, are reduced. This scheme is used in rural or suburban areas where the solar profile is significant and air conditioner is extensively used.